Unveiling the Healing Potential of Avicennia marina: A Mini Review on its Medicinal Marvels - Aymen Abdulateef Alrubaye; Reshad Moradi Balef; Siavash Kalbi; Nader Tanideh (West Kazakhstan Medical Journal, 2024)
Abstract This mini review delves into the therapeutic attributes of Avicennia marina, commonly known as the Grey Mangrove, situated within mangrove ecosystems. Characterized by unique biochemical features, A. marina has captured the attention of the scientific community for its potential medicinal applications. Thriving in intertidal zones amidst salinity fluctuations and environmental stressors, this resilient mangrove species has evolved adaptive mechanisms, leading to the synthesis of secondary metabolites with recognized pharmacological properties. Beyond its immediate relevance in medical research, A. marina emerges as a significant player in environmental health, especially in the context of escalating climate change challenges. The intertidal zones it inhabits face increasing vulnerability to rising sea levels and temperature fluctuations, emphasizing the importance of understanding its adaptive mechanisms for both medicinal and ecological insights. Moreover, A. marina serves as a testament to the intricate interplay between nature and human health. Bioactive compounds found in this mangrove not only hold promise for pharmaceutical applications but also contribute to the burgeoning field of herbal medicine. Integrating traditional knowledge with modern scientific approaches provides a holistic understanding of the Grey Mangrove's therapeutic spectrum, unveiling potential herbal remedies with relevance to contemporary healthcare practices. This dual perspective positions A. marina as a subject of interdisciplinary research, where botanical pharmacology intersects with ecological resilience, addressing both medical and environmental challenges.